Bacillus Calmette-Guérin vaccination at birth: Effects on infant growth. A randomized clinical trial - Kjærgaard, Jesper; Stensballe, Lone Graff; Birk, Nina Marie; Nissen, Thomas Nørrelykke; Thøstesen, Lisbeth Marianne; Pihl, Gitte Thybo; Nielsen, Agnethe Vale; Kofoed, Poul-Erik; Aaby, Peter; Pryds, Ole; Greisen, Gorm (Early human development, 2016)
Bacillus Calmette-Guérin vaccine (BCG) induces a complex, pro-inflammatory immune response. Obesity is associated with low-grade inflammation. The purpose of the study was to test whether BCG at birth has effects on infant growth and body composition. The Danish Calmette Study is a randomized, clinical trial. The study was conducted at three university hospitals and randomized 4262 children of gestational age ≥32weeks to receive BCG within seven days of birth or to a no-intervention control group. Follow-up consisted of clinical examinations. Outcome measures were weight and length at 3months, and weight, length, mid upper-arm circumference, and triceps and subscapular skinfold at 13months. Data collectors were blinded to allocation. Anthropometric measurements were converted to z-scores using WHO reference population. Follow-up was 94% complete at 3 and 13months after birth. The children were bigger than the WHO reference population. There was no effect of BCG on weight z-score at 13months (−0.028 [95% confidence interval: −0.085 to 0.029], p=0.34). There was no effect on weight and length at 3months, or length, mid-upper-arm circumference, or triceps and subscapular skinfold at 13months. In this study, vaccination with BCG at birth did not have effects on child growth or body composition at 13months. www.clinicaltrials.gov, registration number NCT01694108. •BCG vaccination may have non-specific effects on childhood morbidiy and mortality.•This is the first study of BCGs' effect on child growth in a high income setting.•BCG vaccination at birth does not affect child growth or body composition until 13months of age.